SOME OBSERVATIONS ON THE LIBERATION AND VIABILITY OF OOSPORES IN SARGASSUM WIGHTII (GREVILLE) J. AGARDH - Rao, M Umamaheswara; Kaliaperumal, N (Indian Journal of Fisheries, 2011)
Some observations made on the output and viability of oospores in Sargassumwightii are presented. iMiaximum output of healthy spores was observed forseven days in the laboratory experiments, without any periodicity in the Eberationof oospores. Spore-shedding season extends for three months, from November toJanuary, with the highest value in December. In viability experiments 47.6% ofthe sporelings have been found in healthy condition at the end of 60 days.